2020
DOI: 10.1002/jmv.25959
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 in pregnancy: Risk of adverse neonatal outcomes

Abstract: We read with great interest the study by Siyu Chen and colleagues. The authors evaluated the clinical features and outcomes of five pregnant patients with COVID-19 at term, whose delivery was uneventful and led to favorable perinatal outcomes for both mother and neonate. We would like to draw attention to a growing body of evidence that now points towards an under-addressed association between preterm maternal SARS-CoV-2 infection, preterm delivery and adverse neonatal outcomes, which is not reflected in Chen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 10 publications
0
24
0
6
Order By: Relevance
“…Of all the infants reported during the first month of life, most had documented exposure to affected family members [ 13 , 32 ] which emphasizes the importance of controlling horizontal virus transmission from affected family members to the neonate [ 33 ]. While this trend may need revision [ 27 , 34 ], so far, it is encouraging that most COVID-19-positive pregnant women do not transmit the disease to their unborn children. Similarly, there is no evidence that COVID-19-positive pregnant women incur COVID-19 or develop more severe disease than similar-aged women who are not pregnant.…”
Section: Covid-19 In Neonates and Childrenmentioning
confidence: 99%
“…Of all the infants reported during the first month of life, most had documented exposure to affected family members [ 13 , 32 ] which emphasizes the importance of controlling horizontal virus transmission from affected family members to the neonate [ 33 ]. While this trend may need revision [ 27 , 34 ], so far, it is encouraging that most COVID-19-positive pregnant women do not transmit the disease to their unborn children. Similarly, there is no evidence that COVID-19-positive pregnant women incur COVID-19 or develop more severe disease than similar-aged women who are not pregnant.…”
Section: Covid-19 In Neonates and Childrenmentioning
confidence: 99%
“…For SARS-CoV-2, the latest clinical evidence identified two cases of fetal distress among nine monitored pregnancies, although no cases of intrauterine infection have been reported (Chen et al 2020). Mehan et al have also reported adverse perinatal outcomes for pregnant women infected with SARS-CoV-2, but it is unclear whether these results are directly related to SARS-CoV-2 (Mehan et al 2020). Although data available from a limited number of case reports do not indicate the presence of maternal-to-infant transmission of SARS-CoV-2, a study by Zeng et al using reverse transcriptase-polymerase chain reaction (RT-PCR) reports that six infants, of six different mothers with COVID-19, tested positive for SARS-CoV-2-specific antibodies and were also presenting with elevated inflammatory cytokine (IL-6) levels (Zeng et al 2020).…”
Section: The Potential Risk Of Reproductive Complications Caused By Cmentioning
confidence: 99%
“…Con sintomatología presente, se describe con mayor frecuencia tos y fiebre. Para prevenir el contagio intrahospitalario algunos autores recomiendan el test específico de RT-PCR al ingreso al preparto, lo que permite detectar las formas asintomáticas y proteger al feto, al recién nacido y al equipo de salud (16). En presencia de un test positivo, el embarazo, el parto y el recién nacido se consideran de alto riesgo.…”
Section: Covid-19 En La Gestaciónunclassified